Disclosure of Intended Use of Proceeds and Underpricing in Initial Public Offerings - LEONE, ANDREW J.; ROCK, STEVE; WILLENBORG, MICHAEL (Journal of Accounting Research, 2007)
We use the context of a company's initial public offering (IPO) of equity securities as a capital-markets setting to empirically study the economic consequences of endogenous disclosure. In particular, we examine the relation between the extent of dollar detail an IPO issuer provides regarding their intended use of proceeds and first-day underpricing. We document substantial variation in the specificity of this disclosure and find that an increase in such specificity is associated with lower IPO underpricing. Overall, our results suggest that IPOs that provide specific use-of-proceeds disclosures have less ex ante uncertainty, in the sense that these disclosures help investors estimate the dispersion of secondary market values. Our paper contributes to the empirical accounting literature by documenting an association between voluntary disclosure and what is arguably the foremost cost of raising initial equity capital (i.e., IPO underpricing).